2007
DOI: 10.1021/cm702546s
|View full text |Cite
|
Sign up to set email alerts
|

Electron Transfer Mechanisms upon Lithium Deintercalation from LiCoO2 to CoO2 Investigated by XPS

Abstract: Lithium deintercalation of Li x CoO 2 from x ) 1 to x ≈ 0 has been carried out electrochemically. The changes in the electronic structure from LiCoO 2 to CoO 2 have been investigated by X-ray photoelectron spectroscopy (XPS) to bring some new developments about the electron transfer mechanisms upon lithium deintercalation. All available XPS core peaks (Co 2p, Co 3p, Co 3s, O 1s, F 1s, P 2p, C 1s) and valence spectra have been analyzed. The contributions of the electrode material and of the electrode/electrolyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

50
331
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 446 publications
(382 citation statements)
references
References 55 publications
50
331
1
Order By: Relevance
“…Although the valency change of Co could not be clearly resolved by the X-ray photoelectron spectroscopy (XPS) result ( Supplementary Fig. 4) similar to previous work 28 , we believe the oxidation state of Co should be higher than 3 þ after the electrochemical tuning process according to the XRD results. It should be noted that such an electrochemical tuning of crystal structure and oxidation states of Co center can be realized in organic lithium electrolyte, but it does not take place in 0.1 M KOH aqueous electrolyte.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…Although the valency change of Co could not be clearly resolved by the X-ray photoelectron spectroscopy (XPS) result ( Supplementary Fig. 4) similar to previous work 28 , we believe the oxidation state of Co should be higher than 3 þ after the electrochemical tuning process according to the XRD results. It should be noted that such an electrochemical tuning of crystal structure and oxidation states of Co center can be realized in organic lithium electrolyte, but it does not take place in 0.1 M KOH aqueous electrolyte.…”
Section: Resultsmentioning
confidence: 51%
“…The Li 0.5 CoO 2 phase possesses a higher activity than the LiCoO 2 phase, which may originate from the change of the electronic structure. Previous reports [28][29][30][31] have shown that the electron charge transfer resulting from Li þ extraction simultaneously involves cobalt and oxygen, which can both be considered to undergo a partial oxidation process, and that more charge is transferred to the oxygen ions than to the metal ions. Therefore, the enhanced OER activity of De-LiCoO 2 may be attributed to the following possible reasons.…”
Section: Resultsmentioning
confidence: 99%
“…Since only a portion of the photoelectron contribute to the shake-up process, the resulting spectrum shows the normal photoelectron peak along with a small satellite at a slightly higher binding energy. 24 Co 2p 3/2 and 2p 1/2 location in spectrum after sputtering 3606.4 nm (Figure 5b commercial powder, which is used as an internal reference in this study (Figure 5a). 2p core level of Co has an asymmetric shape, comprising of a small shoulder at the higher binding energy.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the satellite peaks at 790 and 805 eV are characteristic of Co 3+ . 18 Thus, these satellite peaks indicate that the cobalt ions in the prepared film are mainly in the trivalent state. In the S 2p spectra of the amorphous thin film, the doublet peaks of S 2p 3/2 and S 2p 1/2 appear at approximately 168.5 and 169.7 eV respectively, and can be assigned to the SO 4 2¹ unit; 19 these peaks are also detected in the case of the milled powder.…”
Section: Resultsmentioning
confidence: 96%